(untitled) (Physical Culture and Sport: Scientific Perspective, 2024)
Modern military conflicts are accompanied by the use of a significant amount of ammunition, which can lead to mine-explosive injuries of various types. Currently, Ukraine is in a full-scale war, so limb injuries as a result of mine-explosive events are of particular interest to medical and rehabilitation specialists due to the numerous peculiarities in their diagnosis, pathogenesis, treatment and recovery process. The purpose of the study: to theoretically substantiate the peculiarities of physical therapy of military personnel with the consequences of mine-explosive injuries of the lower extremities. Research methods. The work used the methods of the theoretical level of research: analysis, comparison, induction, deduction, systematization and generalization of scientific and methodical literature. Work results. The general scientific approach to the physical rehabilitation of soldiers with mine and explosive injuries is based on the implementation of innovative methods, the involvement of multidisciplinary teams of specialists and the constant monitoring of results for the constant improvement of rehabilitation programs. Physical therapy should focus on optimizing the healing process, restoring biomechanical connections between normal and damaged tissues, and controlling pain and limiting activities. One of the main tasks is to restore the functions of the victims in order to return them to an active life and functioning. This sets high standards for care both at the stage of hospitalization and at the stage of further rehabilitation. Conclusions. Thus, effective rehabilitation of servicemen with mine-explosive injuries requires a deep understanding of the specifics of injuries, individual characteristics of the victims, and the use of innovative methods to ensure full recovery of physical and emotional health.